Some Aspects of Ai-Technologies in Education - A. Klyuchnikov, Denis (2021)
The article is mostly theoretical, bears a review character and is devoted to the description of artificial intelligence (AI) and its role in the life of the modern learning society. The article partly goes into the history of Artificial Intelligence development. The definition of ARTIFICIAL INTELLIGENCE is specified; its functions are stated; its benefits are described.